2,2-diphenyl-1-picrylhydrazyl (DPPH) Radical Scavenging Analysis and Antibacterial Activities of Renggak Seed (Amomum Dealbatum Roxb) - Muhlisun Azim; Puspawan Hariadi; Baiq Risma Fatmayanti; Yuyun Febriani; Annisa Rizqita Wazni; Virta Dwi Anggraini (Sinteza, 2025)
Natural sources have complex interaction mechanisms in providing inhibitory effects against various radical reactions and multi-drug resistance (MDR). Amomum dealbatum (Renggak in Lombok) seed phytochemistry and bioactivities have the potential to be investigated. This study aims to explore the bioactivity of extracts and fractions of renggak seeds in reducing reactive oxygen species and inhibiting bacterial growth to overcome MDR. The methods used to determine the level of free radical scavenging and antibacterial activity in this study were the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and agar diffusion methods. The results of the phytochemical tests of the ethanolic extract of Renggak seeds contain triterpenoids, alkaloids, saponins, and phenolics. Meanwhile, in the hexane fraction were found alkaloids, saponins, and phenolics. The results of antibacterial tests on Staphylococcus aureus using the agar diffusion method for ethanol and hexane extracts at concentrations of 20, 40 and 60% were 12.50±1.00, 19.00±0.00, and 21.8±0.76 for ethanol extracts, respectively. The hexane fraction was 5.33±0.57, 10.83±0.57, and 14.33±0.28 mm. For Salmonella sp bacteria, it was 9.00±1.00, 14.16±0.29, and 18.16±1.04 mm for ethanol extracts than was 7.50±0.50, 12.67±0.76, and 15.67±0.76 mm for hexane fractions. Moreover, the ethyl acetate fraction contains triterpenoids, alkaloids, saponins and phenolics which are responsible for giving antioxidant effects with an IC50 value of 66.515±2.37 ppm and is classified as a strong antioxidant to scavenging free radicals of DPPH. The higher the concentration of the fraction, the higher the inhibition of the growth of Salmonella sp and Staphylococcus aureus bacteria. The ability of the extract and fraction to inhibit bacterial growth and reduce free radicals makes renggak seeds very potential for further investigation.